Political Events of February 1917 in the Diocesan Periodicals of Western Siberia - A. A. Valitov; D. Yu. Fedotova (Научный диалог)
The events of February 1917, presented on the pages of the church periodicals of Western Siberia, is examined in the article. The relevance of the study is due to the fact that for the first time in Russian historiography the political upheavals of this period have been analyzed on the basis of materials from regional diocesan records. The authors note that the diocesan records are an important historical source. A detailed analysis of the content of articles of Omsk, Tobolsk, Tomsk periodicals (“Diocesan Gazette”) on the presentation of the political events of February 1917 in them is carried out. The novelty of the research lies in identifying the attitude of the regional clergy to the revolutionary events in the period from February to April 1917. The presented results of the comparative analysis can be grouped according to the chronology and significance of the events that took place. The article concludes that it was during this period that one could hear the opinion of the Russian Orthodox Church on political changes in the country. It is noted that of particular interest were the issues of the relationship between the Church and the Provisional Government, this topic remained the most acute after the fall of the monarchy. It is shown that the representatives of the Russian Orthodox Church wanted to restore historical justice and receive autonomous government and independence from the secular authorities.